Research on detection of transmission line corridor external force object containing random feature targets - Zou, Hongbo; Ye, Ziyong; Sun, Jialun; Chen, Junting; Yang, Qinhe; Chai, Yanhui (Frontiers in Energy Research, 2024)
With the objective of achieving “double carbon,” the power grid is placing greater importance on the security of transmission lines. The transmission line corridor has complex situations with external force targets and irregularly featured objects including smoke. For this reason, in this paper, the high-performance YOLOX-S model is selected for transmission line corridor external force object detection and improved to enhance model multi-object detection capability and irregular feature extraction capability. Firstly, to enhance the perception capability of external force objects in complex environment, we improve the feature output capability by adding the global context block after the output of the backbone. Then, we integrate convolutional block attention module into the feature fusion operation to enhance the recognition of objects with random features, among the external force targets by incorporating attention mechanism. Finally, we utilize EIoU to enhance the accuracy of object detection boxes, enabling the successful detection of external force targets in transmission line corridors. Through training and validating the model with the established external force dataset, the improved model demonstrates the capability to successfully detect external force objects and achieves favorable results in multi-class target detection. While there is improvement in the detection capability of external force objects with random features, the results indicate the need to enhance smoke recognition, particularly in further distinguishing targets between smoke and fog.